Fluvial seed dispersal of riparian trees: transport and depositional processes. Issue 5 (11th November 2015) - Cunnings, Adrienne; Johnson, Edward; Martin, Yvonne
Abstract: Fluvial seed dispersal considers both the transport and deposition of seeds where channel geomorphic structures, hydrology and seed dispersal traits contribute to transport times and depositional locations. This study examines the influence of stream flow patterns on fluvial seed dispersal of buoyant white alder ( Alnus rhombifolia ) seeds by applying a one‐dimensional transport model. Conceptually, the model separates the stream into two components: (i) the main channel where the seeds are transported downstream; and (ii) the transient storage zone where seeds are temporarily detained or deposited on the river bank. Transport processes are characterized by an advection–dispersion equation which is coupled to a transient storage model using an exponential decay term. The model parameters: longitudinal dispersion ( D L ), exchange coefficient ( α ), main channel area ( A ) and storage zone ( A s ) are estimated based on field experiments conducted in a confined, bedrock‐gravel bed river with pool‐riffle morphology located in coastal northern California. The riparian zone is inhabited by Alnus rhombifolia that disperse buoyant seeds in mid‐spring coinciding with the end of the wet, Mediterranean season. Artificial seeds, with similar traits of buoyancy and density to alder seeds, were used to quantify transport times and depositional locations. Preferential deposition resulted in stream reaches with larger A s, high A s / A ratios, and faster exchange coefficients corresponding to divergent stream flow (back‐eddies, re‐circulating flow, flow expansions) caused by geomorphic structures such as the ends of bar/riffle features and bends in the stream. The results demonstrate the importance of transient storage for seed transport and depositional processes. Morphological features that increase a channel's complexity create complex flow structures that detain seeds and provide a greater opportunity for deposition to occur. The model provides a simplification of river hydraulics to represent dispersal dynamics and lends itself to further understanding of hydrochory processes and associated population structure. Copyright © 2015 John Wiley & Sons, Ltd.